Effects of Body Force on the Pulsating Blood Flow in Arteries - Haldar, K.; Ghosh, S.N. (Engineering Transactions, 1993)
The present investigation deals with the study of pulsating blood flow in single arteries in the presence of body force which usually arises unintentionally during travel in a road vehicle, an aircraft or a spacecraft. A blood vessel considered here is assumed to be rigid. The resulting equation which governs the flow field in the tube is one-dimensional and it is solved using the Fourier analysis. The results obtained in this analysis are the expressions for the local energy dissipation and the amplitude coefficients of mean velocity and wall shear stress. The numerical solutions of these results are shown graphically for better understanding of problem.